2016
DOI: 10.1016/j.jcf.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae oropharyngeal colonization in children and adolescents with cystic fibrosis

Abstract: S. pneumoniae carrier state of school-age children and adolescents with CF is more prevalent than previously thought, and pneumococcal conjugate vaccination administered in the first year of life does not reduce the risk of re-colonization in later childhood and adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…We do not have a clear explanation for this finding. It is well-known that influenza vaccination has a role in prevention of pneumococcal infection 22,23 and in our study performed in patients with cystic fibrosis, 24 the majority of whom were vaccinated against influenza, influenza vaccination coverage was similar between carriers and non-carriers.…”
Section: Discussionsupporting
confidence: 50%
“…We do not have a clear explanation for this finding. It is well-known that influenza vaccination has a role in prevention of pneumococcal infection 22,23 and in our study performed in patients with cystic fibrosis, 24 the majority of whom were vaccinated against influenza, influenza vaccination coverage was similar between carriers and non-carriers.…”
Section: Discussionsupporting
confidence: 50%
“…For example, 15 of 318 (4.7%) adults examined in a retrospective study were culture positive for group A streptococcus (GAS) in their sputum, and 7/15 of these patients were suffering from an exacerbation at the time of the positive culture (32), analogous to the observations made for SMG isolates and exacerbation described above. In another study, ϳ20% of the 212 children with CF studied were shown to have detectable Streptococcus pneumoniae when oropharyngeal swab specimens were analyzed by quantitative PCR (33). Interestingly, Dennis and colleagues showed that mucoid variants of S. pneumoniae could be isolated from the sputum of children with CF (32).…”
Section: Is There a Role For Typical Pathogenic Streptococci In Cf?mentioning
confidence: 99%
“…pneumoniae is a Gram-positive coccus that can survive under both aerobic and anaerobic conditions [59]. It causes mucosal and invasive infections in children and adults, most commonly acute otitis media (AOM), community-acquired pneumonia (CAP), and invasive pneumococcal diseases (IPD), such as bacteraemia and meningitis [60][61][62][63][64].…”
Section: Pneumococcal Vaccinationmentioning
confidence: 99%